Evidence for independent peripheral and central age‐related hearing impairment. Issue 9 (16th May 2020) - Bao, Jianxin; Yu, Yan; Li, Hui; Hawks, John; Szatkowski, Grace; Dade, Bethany; Wang, Hao; Liu, Peng; Brutnell, Thomas; Spehar, Brent; Tye‐Murray, Nancy
Abstract: Deleterious age‐related changes in the central auditory nervous system have been referred to as central age‐related hearing impairment (ARHI) or central presbycusis. Central ARHI is often assumed to be the consequence of peripheral ARHI. However, it is possible that certain aspects of central ARHI are independent from peripheral ARHI. A confirmation of this possibility could lead to significant improvements in current rehabilitation practices. The major difficulty in addressing this issue arises from confounding factors, such as other age‐related changes in both the cochlea and central non‐auditory brain structures. Because gap detection is a common measure of central auditory temporal processing, and gap detection thresholds are less influenced by changes in other brain functions such as learning and memory, we investigated the potential relationship between age‐related peripheral hearing loss (i.e., audiograms) and age‐related changes in gap detection. Consistent with previous studies, a significant difference was found for gap detection thresholds between young and older adults. However, among older adults, no significant associations were observed between gap detection ability and several other independent variables including the pure tone audiogram average, the Wechsler Adult Intelligence Scale‐Vocabulary score, gender, and age. Statistical analyses showed little or no contributions from these independent variables to gap detection thresholds. Thus, our data indicate that age‐related decline in central temporal processing is largely independent of peripheral ARHI. Abstract : Certain aspects of central presbycusis such as temporal processing can largely exist independent of peripheral presbycusis.